Kejahatan dan pengadilan internasional / Mangai Natarajan ; penerjemah, Irfan M. Zakhie ; penyunting, M. Rizal - NATARAJAN, Mangai; Irfan M. Zakhie; Rizal, M. (Nusa Media, 2015)
xLvi, 534 hlm. : ilus. ; 23 cm